2021
DOI: 10.24875/ric.19003280
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of the MAD1L1 1673 G:A Polymorphism in Ovarian Adenocarcinomas

Abstract: Background: Ovarian cancer is the most lethal gynecologic cancer. Although most patients respond adequately to the first-line therapy, up to 85% experience a recurrence of disease, which carries a poor prognosis. Mitotic arrest deficiency 1 is a protein that helps in the assembly of the mitotic spindle assembly checkpoint by preventing anaphase until all chromatids are properly aligned. A single-nucleotide polymorphism in the MAD1L1 gene is prevalent in patients with advanced epithelial ovarian cancer and alte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…To investigate whether RAE1 could be a therapeutic target, we performed a comprehensive analysis of 276 genes encoding microtubule‐regulating proteins 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 using TCGA data and evaluated their potential efficacy as a therapeutic target. We calculated the fold change in mRNA expression of each gene in tumor tissues compared to normal tissues, the correlation between mRNA expression and DNA copy number, and whether the high expression group was associated with poor prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate whether RAE1 could be a therapeutic target, we performed a comprehensive analysis of 276 genes encoding microtubule‐regulating proteins 19 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 using TCGA data and evaluated their potential efficacy as a therapeutic target. We calculated the fold change in mRNA expression of each gene in tumor tissues compared to normal tissues, the correlation between mRNA expression and DNA copy number, and whether the high expression group was associated with poor prognosis.…”
Section: Resultsmentioning
confidence: 99%
“…In mitosis, the cell cycle arrest was impaired when MAD1 expression was downregulated by treatment with microtubule stabilizing and microtubule destabilizing agents ( Kienitz et al, 2005 ). Mutation frequencies of the SAC genes remained low, and only rare polymorphisms in MAD1L1 , MAD2L1 , and BUB1b were found in certain cancers involved in the modulation of the cell cycle arrest ( Su et al, 2016 ; Bandala-Jacques et al, 2020 ; Sun et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…We then found a significant difference in the frequency for MAD1L 1 rs1801368 C>T between cases and controls. In some studies, the polymorphism in the MAD1L1 rs1801368 T allele has been found to be associated with certain kinds of cancer that showed somatic cell aneuploidy ( Santibanez et al, 2013 ; Zhong et al, 2015 ; Bandala-Jacques et al, 2020 ). However, interestingly, our result of MAD1L1 rs1801368 C>T was contrary to those reports.…”
Section: Discussionmentioning
confidence: 99%